Duncan Campbell Scott and Maurice Maeterlinck - Bentley, D.M.R (Studies in Canadian Literature)

(untitled) (None, 1996)
Maurice Maeterlinck, hailed in 1892 as "the Belgian Shakespeare," influenced Canadian artistic circles around the turn of the century. A Canadian writer who appears to have been particularly receptive to the influence of Maeterlinck is Duncan Campbell Scott. Evidence suggests Scott drew upon the mystical positivism of Maeterlinck's The Treasure of the Humble in writing "the Forsaken," "On the Way to the Mission" and "Labor and the Angel".